The Role of Project-Based Learning (PjBL) Models in Improving the Ability to Organize Wrestling Sports Competitions for Physical Education Students FKIP Tanjungpura University - Muhammad Fachrurrozi Bafadal; Mimi Haetami (Universitas Bengkulu, 2021)
Improving the ability to organize sports competitions in wrestling courses for physical education students in semester 5 of 2021 by using the Project-based learning (PjBL) model is the goal of this research. This research method is Class Action (CAR) there are 2 cycles, each cycle 2 meetings are consisting of planning, action, observation, and reflection. The sample of this study amounted to 12 students and used purposive sampling. The results of this study indicate, during the pre-cycle to cycle II, there was an increase in the ability to organize sports competitions. In the pre-cycle, it has not shown the ability to organize sports matches by 461 points with a percentage of 38.41% and is included in the very poor category, an increase in the ability to organize sports matches in the first cycle is 749 points with a percentage of 62.41% moving up to the moderate category and continues increased in the second cycle by 1001 points with a percentage of 83.41% and continued to climb into the Good category. The conclusion in this study is that the ability to organize wrestling competitions for physical education students, FKIP Tanjungpura University can be improved through the Project-Based Learning (PJBL) learning model as seen from the percentage of cycle II of 83.41% with the Good category, this means that physical education.